Coupling natural-social models can better quantify the interactions in achieving carbon neutrality in China - Tianpeng Wang; Yixiong Lu; Fei Teng; Xiliang Zhang; Xiaoye Zhang; Min Wei; Tongwen Wu; Deying Wang; Jing Sun; Junting Zhong (Environmental Research Letters)
Human activities have greatly altered Earth’s radiative balance, necessitating assessments that couple natural and social systems to address the resulting impacts and interactions. However, traditional Earth System Models (ESMs) and integrated assessment models often split to simulate changes in the two systems and neglect the feedback between these systems, limiting our understanding of the pathways to carbon neutrality, the associated global warming level and climate change impacts. This study constructs a coupled natural-social systems framework to bridge this gap, integrating the China-in-global energy model with the Beijing Climate Center ESM version 1. The results show that bidirectional feedbacks in the natural-social system increase the demand for electricity under China’s carbon neutrality target, increasing the pressure to reduce emissions and driving up the carbon prices. Meanwhile, carbon neutrality does not eliminate all negative climate impacts and can substantially reduce the economic output of climate-vulnerable sectors in China, highlighting the need for early adaptation measures. This study emphasizes the importance of planning China’s climate neutrality pathways from a coupled natural-social system perspective.